Bioprosthetic Total Artificial Heart in Autoregulated Mode Is Biologically Hemocompatible: Insights for Multimers of von Willebrand Factor. Issue 4 (10th February 2022) - Poitier, Bastien; Chocron, Richard; Peronino, Christophe; Philippe, Aurélien; Pya, Yuri; Rivet, Nadia; Richez, Ulysse; Bekbossynova, Mahabbat; Gendron, Nicolas; Grimmé, Marc; Bories, Marie Cécile; Brichet, Julie; et al.
Abstract : Background: Carmat bioprosthetic total artificial heart (Aeson; A-TAH) is a pulsatile and autoregulated device. The aim of this study is to evaluate level of hemolysis potential acquired von Willebrand syndrome after A-TAH implantation. Methods: We examined the presence of hemolysis and acquired von Willebrand syndrome in adult patients receiving A-TAH support (n=10) during their whole clinical follow-up in comparison with control subjects and adult patients receiving Heartmate II or Heartmate III support. We also performed a fluid structure interaction model coupled with computational fluid dynamics simulation to evaluate the A-TAH resulting shear stress and its distribution in the blood volume. Results: The cumulative duration of A-TAH support was 2087 days. A-TAH implantation did not affect plasma free hemoglobin over time, and there was no association between plasma free hemoglobin and cardiac output or beat rate. For VWF (von Willebrand factor) evaluation, A-TAH implantation did not modify multimers profile of VWF in contrast to Heartmate II and Heartmate III. Furthermore, fluid structure interaction coupled with computational fluid dynamics showed a gradually increase of blood damage according to increase of cardiac output ( P <0.01), however, the blood volume fraction that endured significant shear stresses was always inferior to 0.03% of the volume for both ventricles in all regimens tested. An inverse association between cardiac output, beat rate, and high-molecular weight multimers ratio was found. Conclusions: We demonstrated that A-TAH does not cause hemolysis or AWVS. However, relationship between HMWM and cardiac output depending flow confirms relevance of VWF as a biological sensor of blood flow, even in normal range.